Method for enhancing stability and heavy metal removal activity of micron zero-valent iron through modification of sodium thioglycollate, product and application

Through the mechanochemical sodium thioglycolate modification process, the problem of insufficient heavy metal removal activity and stability of micron zero-valent iron is solved, the effect of efficiently removing a variety of heavy metals in water is achieved, and high stability is maintained during wet storage and transportation.

CN119346864AActive Publication Date: 2025-01-24SHANGHAI JIAOTONG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411360369.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-24
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The existing micron zero-valent iron has poor heavy metal removal activity and insufficient stability, resulting in poor results in heavy metal pollution control.

Method used

Through the mechanochemical sodium thioglycolate modification process, micron zero-valent iron and sodium thioglycolate powder are ball milled to change its morphology and thin the iron oxide shell, thereby exposing more active sites and enhancing the release of iron core electrons and heavy metals. adsorption capacity.

Benefits of technology

Significantly improve the heavy metal removal activity and stability of micron zero-valent iron, increase the heavy metal removal rate and capacity, and maintain efficient removal performance during wet storage and transportation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119346864A_ABST
    Figure CN119346864A_ABST
Patent Text Reader

Abstract

The invention relates to a method for enhancing stability of micron zero-valent iron and heavy metal removal activity through sodium thioglycolate modification, a product and application. The method comprises the following steps: mixing sodium thioglycolate powder with commercial micron zero-valent iron, and carrying out ball milling; and finally, the flaky zero-valent iron material with high stability and high heavy metal removal activity can be obtained, wherein the flaky thickness of the flaky zero-valent iron material is about 300nm, and the content of zero-valent iron is greater than 90%. The prepared mechanochemical sodium thioglycollate modified zero-valent iron material breaks through passivation and inertness of original micron zero-valent iron, the heavy metal removal activity of the micron zero-valent iron is remarkably improved, and the heavy metal removal rate of the micron zero-valent iron is improved by 16.7-88.0 times compared with that of common ball-milled zero-valent iron. The sodium thioglycolate modified zero-valent iron prepared by the method has excellent wet storage and transportation stability, and more than 95% of 10ppm CrIV can still be removed within 1h after 60 days of storage and transportation. The method provided by the invention is simple and efficient in process, low in cost and environment-friendly, and lays a technical foundation for safe and efficient low-cost macro preparation of the zero-valent iron.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of environmental chemistry, and specifically relates to a method, product and application of sodium thioglycolate modified micron zero-valent iron to enhance stability and heavy metal removal activity, and is a method for preparing zero-valent iron with high stability and high heavy metal removal activity. The material prepared by the method of the present invention is suitable for treating Ni II Cr VI 、Cd II , Pb II , Hg II and Sb III And other heavy metal pollution. Background Art

[0002] Heavy metal pollution is a major environmental problem worldwide. Further strengthening the control of heavy metal pollutant emissions and taking concrete actions to fight the battle against pollution are very important for ecological environmental protection and heavy metal pollution prevention and control. Improving the ability to control heavy metal pollution will provide theoretical and technical support for improving the quality of heavy metal pollution environments.

[0003] Zero-valent iron is an important environmental remediation material that can simultaneously achieve heavy metal reduction and fixation. Micronized zero-valent iron (1-100 μm) (mZVI) is widely used for heavy metal removal due to its easy production and low cost. However, the heavy metal removal performance of mZVI is limited by its thick inert oxide shell, which physically hinders the outward transmission of iron core electrons and chemically inhibits the surface adsorption of heavy metals, resulting in poor heavy metal removal activity of mZVI. Therefore, the development of green and efficient modification strategies to simultaneously enhance the electron transfer of the iron core and the adsorption of heavy metals by the oxide shell is crucial for the preparation of high-performance mZVI. Although the prior art has used oxalic acid, 2-pyridinecarboxylic acid, etc. to modify zero-valent iron by ball milling, the existing methods still have problems such as insufficient product stability and easy deactivation.

[0004] In addition, the development of simple preparation methods is also important for the large-scale preparation of functional micron zero-valent iron. Mechanochemistry can generate local pressure and heat to deform mZVI and promote chemical reactions on its surface. It is a promising preparation method that is easy to industrialize the production of functional materials. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a method, product and application of sodium thioglycolate modification to enhance the stability and heavy metal removal activity of micron zero-valent iron. The present invention aims to solve the problems of low activity and poor stability of mZVI and provide a simple and pollution-free mechanochemical sodium thioglycolate (HS-CH2COO –The present invention changes the morphology of mZVI and thins the thickness of the iron oxide shell through mechanochemical TG modification, thereby exposing more active sites on mZVI to bind TG, and the heat generated by mechanical friction and collision further promotes the electron-withdrawing carboxyl (-COO – ) groups and the inert oxide shell to establish more strong covalent bonds, thereby accelerating the release of iron core electrons and more effectively enhancing the adsorption of surface heavy metals through the metal (d)-sulfur (p) orbital hybridization between its thiol (-SH) group and heavy metal ions. me -mZVI), whose zero-valent iron content reaches 90.2%, and the adsorption and reduction capacity of heavy metals is significantly improved, among which Cr IV 、Ni II The removal capacity is up to 7.7 mg Cr g -1 Fe and 580.4mg Ni g - 1 In addition, the TG-modified mZVI prepared by the present invention has high water-based wet storage stability. After 60 days of wet storage and transportation, more than 95% of 10ppm Cr can still be removed within 1 hour. IV .

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] The first object of the present invention is to provide a method for modifying micronized zero-valent iron with sodium thioglycolate to enhance its stability and heavy metal removal activity.

[0008] In order to achieve the above-mentioned object, the present invention provides a mechanochemical sodium thioglycolate modification process, in which micron zero-valent iron and sodium thioglycolate powder are ball-milled in a ball mill for a period of time to obtain thin flake micron zero-valent iron (thickness ≤ 300nm), namely, sodium thioglycolate modified micron zero-valent iron (mechanical chemical sodium thioglycolate modified micron zero-valent iron).

[0009] According to the above scheme, the mass percentage of sodium thioglycolate used in the micron zero-valent iron is 1% to 5%.

[0010] According to the above scheme, the ball milling time is 2h to 10h, and the ball milling speed is 300rpm to 800rpm.

[0011] According to the above scheme, the ball mill includes a planetary ball mill, a horizontal sand mill and other mechanical equipment that crushes materials based on the principle of ball mill medium impact.

[0012] According to the above scheme, mechanochemical sodium thioglycolate modified zero-valent iron can be directly applied to aqueous Ni II Cr VI 、Cd II, Pb II , Hg II and Sb III Control of heavy metal pollution.

[0013] Furthermore, the method comprises the following steps:

[0014] Sodium thioglycolate powder is mixed with commercial micron zero-valent iron and dry-milled to obtain sodium thioglycolate-modified micron zero-valent iron, wherein the sodium thioglycolate-modified micron zero-valent iron is a thin flaky zero-valent iron with a layer thickness of about 300 nm and a zero-valent iron content of >90%, and has a high heavy metal removal activity.

[0015] Furthermore, the mass percentage of the sodium thioglycolate used in the micron zero-valent iron is 1% to 5%.

[0016] Furthermore, the dry ball milling time is 2 hours to 10 hours, and the ball milling speed is 300 rpm to 800 rpm.

[0017] Furthermore, the dry ball milling is performed using a ball mill, and the material of the ball milling medium includes zirconium oxide, stainless steel, and silicon carbide.

[0018] Furthermore, the particle size of the ball mill medium is in the range of 0.3 mm to 10 mm.

[0019] Furthermore, the ball mill refers to a mechanical device that crushes materials based on the principle of ball milling medium impact, including but not limited to a planetary ball mill and a horizontal sand mill.

[0020] Furthermore, the high heavy metal removal activity means that the flaky zero-valent iron has a higher heavy metal removal activity than the micron zero-valent iron prepared by ball milling, and the removal rate is ten to dozens of times that of the latter.

[0021] The second object of the present invention is to provide a sodium thioglycolate modified micron zero-valent iron, which is prepared by a method of using sodium thioglycolate to modify and enhance the stability and heavy metal removal activity of micron zero-valent iron.

[0022] Furthermore, the sodium thioglycolate-modified micronized zero-valent iron is a thin-sheet zero-valent iron with a thickness of about 300 nm and a zero-valent iron content of >90%, and has a high heavy metal removal activity.

[0023] The second object of the present invention is to provide an application of sodium thioglycolate modified micron zero-valent iron, wherein the sodium thioglycolate modified micron zero-valent iron is prepared by a method of sodium thioglycolate modification to enhance the stability and heavy metal removal activity of micron zero-valent iron, and the sodium thioglycolate modified micron zero-valent iron is applied to the treatment of heavy metal pollution in water bodies, and the sodium thioglycolate modified zero-valent iron can be directly applied to the treatment of heavy metal pollution in water bodies. IICr VI 、Cd II , Pb II , Hg II and Sb III Control of heavy metal pollution.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. For the first time, the stability and heavy metal removal activity of micronized zero-valent iron are enhanced simultaneously by mechanochemical sodium thioglycolate modification. The micronized zero-valent iron flakes prepared by the present invention have a small thickness (about 300 nm), a high zero-valent iron content (>90%), and a high water-based wet storage stability. Compared with the micronized zero-valent iron (mZVI) prepared by ordinary ball milling, the heavy metal removal ability is significantly enhanced.

[0026] 2. The present invention is the first to use a bifunctional environmentally friendly mineral flotation agent, sodium thioglycolate, to modify the surface of micron zero-valent iron. The raw materials are green, environmentally friendly, cheap and easily available.

[0027] 3. The method provided by the present invention is simple, efficient, low-cost and environmentally friendly, laying a technical foundation for the safe, efficient and low-cost macro-quantification preparation of zero-valent iron. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is the XRD spectrum of the mechanochemical sodium thioglycolate modified micron zero-valent iron prepared by the present invention.

[0029] Figure 2 Scanning electron microscope (SEM) images of the mechanochemical sodium thioglycolate modified micronized zero-valent iron prepared in the present invention and the micronized zero-valent iron prepared in the comparative example. (a) mZVI, (b) TG me -mZVI.

[0030] Figure 3 The atomic force microscope (AFM) test results of the mechanochemical sodium thioglycolate modified micron zero-valent iron prepared by the present invention. me -mZVI (a) AFM image and (b) corresponding height distribution along the line, (c) AFM 3D image.

[0031] Figure 4 High-resolution transmission electron microscopy (HRTEM) images of the mechanochemical sodium thioglycolate modified micronized zero-valent iron prepared in the present invention and the micronized zero-valent iron prepared in the comparative example. (a) mZVI, (b) TG me -mZVI.

[0032] Figure 5The specific surface area analysis diagram of the mechanochemical sodium thioglycolate modified micronized zero-valent iron prepared in the present invention and the micronized zero-valent iron prepared in the comparative example. (a) mZVI and TG me -N2 adsorption / desorption isotherms of mZVI and (b) the corresponding specific surface area.

[0033] Figure 6 This is a comparison chart of the zero-valent iron content of the mechanochemical sodium thioglycolate modified sample (mechanochemical sodium thioglycolate modified micron zero-valent iron) prepared by the present invention and the micron zero-valent iron prepared in the comparative example.

[0034] Figure 7 Figure 2 shows the heavy metal removal effect of the mechanochemical sodium thioglycolate modified micron zero-valent iron prepared in the present invention and the micron zero-valent iron prepared in the comparative example. (a) Heavy metal concentration change curve, (b) mZVI kinetic fitting, (c) TG me -mZVI kinetic fitting, (d) kinetic constants K(TG me -mZVI) / K(mZVI)

[0035] Figure 8 Heavy metal Cr in micron zero-valent iron modified by mechanochemical sodium thioglycolate prepared by the present invention IV and Ni II Removal capacity of Cr IV , (b) Ni II .

[0036] Fig. 9 The mechanochemical sodium thioglycolate modified micron zero-valent iron prepared by the present invention removes heavy metal Cr after 60 days of water-based wet storage and transportation IV The effect of aging was evaluated (before aging, it was before 60 days of water-based wet storage and transportation; after aging, it was after 60 days of water-based wet storage and transportation). (a) Zero-valent iron content before and after aging, (b) Hexavalent chromium removal rate before and after aging.

[0037] Fig.10 The present invention is a schematic flow chart of the method for modifying micronized zero-valent iron with sodium thioglycolate to enhance its stability and heavy metal removal activity. DETAILED DESCRIPTION

[0038] The invention content of the present invention is described in detail below through specific implementation cases. The specific embodiments described are only used to explain the present invention and are not used to limit the present invention. The features such as component models, material names, connection structures, control methods, etc. that are not clearly described in this technical solution are regarded as common technical features disclosed in the prior art.

[0039] The present invention relates to a method, product and application of sodium thioglycolate modified micron zero-valent iron to enhance stability and heavy metal removal activity. The method comprises the following steps: mixing sodium thioglycolate powder with commercial micron zero-valent iron and ball milling, and finally obtaining a sheet zero-valent iron material with a sheet thickness of about 300 nm and a zero-valent iron content of more than 90%, high stability and high heavy metal removal activity. The mechanochemical sodium thioglycolate modified zero-valent iron material prepared by the method breaks the passivation and inertness of the original micron zero-valent iron, and can significantly improve the heavy metal (Ni II Cr VI 、Cd II , Pb II , Hg II and Sb III ) removal activity, and its heavy metal removal rate is 16.7 to 88.0 times higher than that of ordinary ball-milled zero-valent iron. In addition, the sodium thioglycolate-modified zero-valent iron prepared by this method has excellent wet storage and transportation stability. After 60 days of storage and transportation, more than 95% of 10ppm Cr can still be removed within 1 hour. IV The method provided by the present invention is simple, efficient, low-cost and environmentally friendly, and lays a technical foundation for the safe, efficient and low-cost macro-quantification preparation of zero-valent iron.

[0040] Example

[0041] Preparation of zero-valent iron microstructures modified by sodium thioglycolate using mechanochemical methods

[0042] like Fig.10 As shown, 5 g of commercial 400 mesh zero-valent iron and 0.12 g of sodium thioglycolate powder were placed in a ball mill, and after adding ball milling beads, a planetary ball mill was used in this embodiment to perform ball milling at a speed of 500 rpm for 5 h to obtain mechanochemical sodium thioglycolate modified micron zero-valent iron (TG me -mZVI). X-ray diffraction (XRD) results showed that mechanochemical TG modification did not change the conformation of zero-valent iron ( Figure 1 ). Scanning electron microscopy (SEM) ( Figure 2 ) and atomic force microscopy (AFM) ( Figure 3 ) The image shows that TG me -mZVI has a deformed flake-like morphology with a thickness of about 300 nm, while mZVI mechanically prepared without TG (comparative example) has an irregular spherical morphology. In addition, high-resolution transmission electron microscopy (HRTEM) revealed that TG me -mZVI oxide layer lattice spacing is 0.198, 0.247 and 0.295nm, respectively, which matches the (400), (311) and (220) atomic planes of Fe2O3 ( Figure 4 More importantly, this mechanochemical process reduced the shell size of mZVI from 13 nm to 4 nm ( Figure 4 ), so that its surface area increases from 0.14m 2 / g increased to 2.60m 2 / g( Figure 5 ). The flakes expose more active sites on mZVI to bind TG, while the heat generated by mechanical friction and collision further promotes the formation of strong covalent bonds between TG and mZVI.

[0043] The zero-valent iron content of the material was further analyzed. The specific steps were as follows: 0.1 g of zero-valent iron material was weighed and placed in a glass bottle. After adding sufficient 1+1 hydrochloric acid, the glass bottle was immediately sealed. After the iron powder was completely dissolved, the hydrogen content in the glass bottle was measured to obtain the zero-valent iron content of the sample. Figure 6 As shown, the content of zero-valent iron modified by mechanochemical sodium thioglycolate in this embodiment is about 90.2%, which indicates that the mechanical sodium thioglycolate modification process will not cause excessive loss of zero-valent iron.

[0044] Comparative Example

[0045] Preparation of micronized zero-valent iron

[0046] 5 g of commercial 400-mesh zero-valent iron was placed in a ball mill, and after adding ball mill beads, a planetary ball mill was used in this comparative example to perform ball milling at a speed of 500 rpm for 5 h to obtain micron zero-valent iron (mZVI).

[0047] Test Case

[0048] Evaluation of the effect of mechanochemical sodium thioglycolate process on efficient removal of heavy metals from water using micronized zero-valent iron

[0049] 50 mL of heavy metal aqueous solution of different concentrations was poured into a 100 mL conical flask, and 50 mg of zero-valent iron sample (1.0 g / L) was added thereto. The zero-valent iron samples were TG prepared in Example 1, me -mZVI and comparative example mZVI were placed on a shaker (200 rpm) for heavy metal removal experiments ([Ni II / Cd II / Pb II / Hg II ]0=20ppm,[Cr VI ]0=10ppm,[Sb III ]0=2ppm). In order to simulate the anoxic environment of groundwater, all reactions were carried out in a nitrogen atmosphere. Sampling was performed at regular intervals and the heavy metal concentration was measured using inductively coupled plasma. Figure 7 The kinetic analysis showed that TG me -mZVI followed a pseudo-first-order reaction to remove heavy metals, Cr VI 、Ni II , Hg II , PbII 、Cd II and Sb III The rate constants of TG were 69.4, 88.0, 49.7, 32.6, 16.7 and 30.2 times that of mZVI. me -mZVI's excellent heavy metal removal performance prompted the applicant to explore its heavy metal removal capacity. IV and Ni II The capacity is 7.7 mg Cr g -1 Fe and 580.4mg Ni g -1 Fe, 8.6 and 17.1 times that of mZVI, respectively ( Figure 8 ). Mechanochemical sodium thioglycolate modification significantly increased the activity of zero-valent iron and enhanced the removal capacity of heavy metals.

[0050] Mechanochemical sodium thioglycolate modification process achieves high stabilization effect of zero-valent iron materials

[0051] In order to explore the mechanochemical sodium thioglycolate modification preparation of the TG me The stability of mZVI in wet storage in water was studied by TG under two storage methods. me -mZVI stability test. Water-based wet storage: Measure 50 mL of deionized water and place it in a 300 mL glass bottle, add 0.1 g of TG me -mZVI, use argon to remove oxygen from the salt water bottle, and then seal the glass bottle. Because there is no oxygen in the system, the loss of zero-valent iron is caused by the hydrogen evolution reaction with water, so the loss of zero-valent iron can be calculated based on the hydrogen concentration in the salt water bottle. The experimental results are as follows Fig. 9 As shown, the flake zero-valent iron (TG me The loss of -mZVI was only 14.3% within 60 days, while maintaining the removal performance of hexavalent chromium. This shows that the mechanochemical sodium thioglycolate modification process simultaneously achieved the stabilization of zero-valent iron.

[0052] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for modifying micronized zero-valent iron with sodium thioglycolate to enhance its stability and heavy metal removal activity, characterized in that: The method comprises the following steps: Sodium thioglycolate powder is mixed with micron zero-valent iron and dry ball milled to obtain sodium thioglycolate-modified micron zero-valent iron, wherein the sheet thickness of the sodium thioglycolate-modified micron zero-valent iron is ≤300nm, the zero-valent iron content is >90%, and the heavy metal removal activity is high.

2. The method according to claim 1, characterized in that: The mass percentage of the used sodium thioglycolate to the micron zero-valent iron is 1% to 5%.

3. The method according to claim 1, characterized in that: The ball milling time of the dry ball milling is 2h to 10h, and the ball milling speed is 300rpm to 800rpm.

4. The method according to claim 1, characterized in that: The dry ball milling is carried out using a ball mill, and the materials of the ball milling medium include zirconium oxide, stainless steel and silicon carbide.

5. The method according to claim 4, characterized in that: The particle size range of the ball mill medium is 0.3 mm to 10 mm.

6. The method according to claim 4, characterized in that: The ball mill is a mechanical device that crushes materials based on the principle of ball milling medium impact, and is selected from a planetary ball mill and a horizontal sand mill.

7. The method according to claim 1, characterized in that: The high heavy metal removal activity means that the flaky zero-valent iron has a higher heavy metal removal activity than the micron zero-valent iron prepared by ball milling, and the removal rate is ten to dozens of times that of the latter.

8. A sodium thioglycolate-modified micronized zero-valent iron prepared by the method according to any one of claims 1 to 7, characterized in that: The sodium thioglycolate-modified micronized zero-valent iron is converted into flaky zero-valent iron.

9. An application of sodium thioglycolate modified micronized zero-valent iron prepared by the method according to any one of claims 1 to 7, characterized in that: The sodium thioglycolate-modified micronized zero-valent iron is applied to the treatment of heavy metal pollution in water bodies.

10. The use according to claim 9, characterized in that: The heavy metals include Ni II Cr VI 、Cd II , Pb II , Hg II and Sb III One or more of .

Citation Information

Patent Citations

  • Method for efficiently removing heavy metal ions on basis of ball-milled oxalated zero-valence iron

    CN108911101A

  • Zero-valent iron agent modified by aromatic carboxylic acid, and preparation method and application thereof

    CN113371809A

  • A filter material having a function of adsorbing and fixing arsenic and heavy metals

    US20160052800A1

  • Effervescent zero-valent iron compositions and method of remediation of pollutants from aqueous solutions

    WO2018153389A1